2014
DOI: 10.5005/jp-journals-10008-1166
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laser Iridoplasty in the Management of Angle Closure Mechanisms other than Pupillary Block

Abstract: Purpose: To investigate the treatment outcomes of argon laser peripheral iridoplasty (ALPI) in angle closure mechanisms other than pupillary block.Methods: We conducted a comprehensive chart review to evaluate consecutive patients who underwent ALPI due to unsuccessful laser iridotomy (whenever the angles remained occludable) between July 2009 and April-2012. An occludable angle was defined as the posterior trabecular meshwork not visible for ≤180° without indentation on dark room gonioscopy. Eyes with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A preliminary study found that immediate ALPI can be used safely and effectively in the first-line management to lower IOP [28]. Vitor et al suggested that ALPI was a useful procedure independent of the underlying mechanism, leading to angle widening and a moderate IOP reduction in patients with occludable angles [29]. The results showed the rapidity and strength of ALPI in the first 2 hours after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study found that immediate ALPI can be used safely and effectively in the first-line management to lower IOP [28]. Vitor et al suggested that ALPI was a useful procedure independent of the underlying mechanism, leading to angle widening and a moderate IOP reduction in patients with occludable angles [29]. The results showed the rapidity and strength of ALPI in the first 2 hours after treatment.…”
Section: Discussionmentioning
confidence: 99%